Stroke-induced and progressive forms of apraxia of speech. (3rd March 2022) - Code, Chris; Tree, Jeremy; Ball, Martin J.
Abstract : Background: Stylistic differences in language use, as described by sociolinguists, have also been shown to occur in disordered speech and language. In this article, we describe apraxia of speech, and compare stroke-induced and progressive forms of this neurogenic disorder. Method: Audio recordings were made of a client, CS, who had progressive apraxia of speech and progressive nonfluent aphasia. Information from control participants was also available, and use was made of published data from clients with stroke-induced apraxia of speech. Results: A range of results are reported, but in particular the comparative difficulty of spontaneous connected speech as compared to reading or repetition for the client with progressive apraxia of speech. This differed from the findings of those with apraxia of speech from stroke, in that connected speech was much more difficult in the progressive form of the disorder. Discussion/conclusion: We discuss the importance of obtaining a wide range of speech styles when collecting data from clients with a range of communication problems, and how – in the specific case of apraxia of speech – these style differences aid in analysis and diagnosis.